Comparative Structural and Biophysical Investigation of Lycosa erythrognatha Toxin I (LyeTx I) and Its Analog LyeTx I-b - Amanda Neves de Souza; Gabriele de Azevedo Cardoso; Lúcio Otávio Nunes; Christopher Aisenbrey; Evgeniy Salnikov; Kelton Rodrigues de Souza; Ahmad Saad; Maria Elena de Lima; Jarbas Magalhães Resende; Burkhard Bechinger; Rodrigo Moreira Verly (Antibiotics)
Background/Objectives: This study investigates the structural and biophysical properties of the wild-type antimicrobial peptide LyeTx I, isolated from the venom of the spider Lycosa erythrognatha, and its analog LyeTx I-b, designed to enhance antibacterial activity, selectivity, and membrane interactions by the acetylation and increased amphipathicty. Methods: To understand the mechanisms behind these enhanced properties, comparative analyses of the structural, topological, biophysical, and thermodynamic aspects of the interactions between each peptide and phospholipid bilayers were evaluated. Both peptides were isotopically labeled with 2H3-Ala and 15N-Leu to facilitate structural studies via NMR spectroscopy. Results: Circular dichroism and solid-state NMR analyses revealed that, while both peptides adopt α-helical conformations in membrane mimetic environments, LyeTx I-b exhibits a more amphipathic and extended helical structure, which correlates with its enhanced membrane interaction. The thermodynamic properties of the peptide–membrane interactions were quantitatively evaluated in the presence of phospholipid bilayers using ITC and DSC, highlighting a greater propensity of LyeTx I-b to disrupt lipid vesicles. Calcein release studies reveal that both peptides cause vesicle disruption, although DLS measurements and TEM imaging indicate distinct effects on phospholipid vesicle organization. While LyeTx I-b permeabilizes anionic membrane retaining the vesicle integrity, LyeTx I promotes significant vesicle agglutination. Furthermore, DSC and calcein release assays indicate that LyeTx I-b exhibits significantly lower cytotoxicity toward eukaryotic membranes compared to LyeTx I, suggesting greater selectivity for bacterial membranes. Conclusions: Our findings provide insights into the structural and functional modifications that enhance the antimicrobial and therapeutic potential of LyeTx I-b, offering valuable guidance for the design of novel peptides targeting resistant bacterial infections and cancer.